Statistical shape refinement and genetic algorithm calibration of design response spectra based on strong-motion records - Xin Han; Chaoyu Chang; Jingshan Bo; Shun Yang; Qiangguo Song; Shaopeng Wang; Mei Guo (PLoS ONE, 2026)
Ground-motion parameters for different site conditions are conventionally prescribed in seismic design codes worldwide, based on post-earthquake damage surveys and statistical analyses of strong-motion databases. Design response spectra thus constitute the primary basis for engineering aseismic design, yet their shapes and characteristic parameters differ markedly among national codes. Systematic computations reveal that code-specified spectral shapes deviate appreciably from recorded earthquake spectra, providing an incomplete representation of site-specific ground-motion characteristics.To address this limitation, 1227 horizontal acceleration records were compiled and classified by magnitude, source distance and site class. Mean dynamic amplification spectra were computed for each subset, and numerical computation were performed to derive an improved analytical expression for the design spectrum. A genetic-algorithm-based calibration procedure was subsequently developed to determine optimal model parameters. The applicability of the proposed approach was examined by calibrating spectra for four independent strong-motion records; spectral parameters obtained with the improved shape were compared with those derived from the conventional code spectrum.Results demonstrate that the refined spectral form captures the frequency-dependent characteristics of earthquake response spectra more accurately than existing representations. The proposed calibration framework offers a valuable reference for advancing design-response-spectrum studies and for the potential updating of seismic design codes.